Sharp Estimates of m-Linear p-Adic Hardy and Hardy-Littlewood-Pólya Operators - Qingyan Wu (Journal of Applied Mathematics, 2011)
The sharp estimates of the m-linear p-adic Hardy and Hardy-Littlewood-Pólya operators on Lebesgue spaces with power weights are obtained in this paper.